A COMPARATIVE STUDY BETWEEN SOLID AND LIQUID CULTURES RELATIVE TO CALLUS GROWTHAND SOMATIC EMBRYO FORMATION IN DATE PALM (PHOENIX DACTYLIFERA L.) CV. ZAGHLOOL - Ibraheem , Y.; Pinker, I.; Böhme, M. (Emirates Journal of Food and Agriculture, 2013)
Tissue culture techniques enable mass propagation of elite cultivars of date palm (Phoenix dactylifera L.). The main limitations for date palm in vitro multiplication are the low rates achieved using solidified medium and the long period needed to produce acclimatized plantlets. This research focuses on the comparison between different culture types and plant growth regulator (PGR) combinations on callus growth and somatic embryo formation of cv. Zaghlool. For callus growth, 200 mg friable embryogenic callus dispensed in Rasotherm and Phytacon flasks containing 200 ml liquid (100 rotations per minute) and in temporary immersion system, RITA® bioreactor (5 min immersion every 12 h), were compared with cultures grown on 200 ml solidified medium. For somatic embryo formation, 500 mg of friable embryogenic callus grown in Erlenmeyer flasks filled with 50 ml liquid or solid MS medium. The medium was supplemented with 0.1 mg l-1 Naphthaleneacetic acid (NAA), 1.5 g l-1 activated charcoal (AC) with or without 0.05 mg l-1 6-Benzyl amino purine (BAP) compared to PGR-free medium. Results proved that cell suspension cultures produced the highest callus fresh mass as compared to the other systems tested, and the callus fresh mass reached 4 g after 16 weeks. The temporary immersion system did not significantly enhance the fresh mass of callus compared to the solidified medium. For somatic embryo induction, the number of somatic embryos increased in cell suspensions 6-16 fold compared to the solidified medium. Using liquid MS medium enriched with 0.1 mg l-1 NAA and 1.5 g l-1 AC gave rise to the highest number of somatic embryos formed from 500 mg initial callus: 160 embryos. The number of somatic embryos was also affected by the callus source. The calli induced from leaflet segments excised from converted somatic embryos resulted in a lower somatic embryo number than those of shoot tip origin with about 60 somatic embryos per 500 mg callus. The formation of somatic embryos using liquid medium required only 6 weeks, thus considerably reducing the previously reported period of 18 weeks which is required for somatic embryo formation using solidified media.